Evaluation of prophylactic effect of herbal formulation In streptozotocin and HFHF diet induced Diabetes and its complication - JAYSHREE S. DAWANE; VIJAYA A. PANDIT; PALLAWI S. KHATAVKAR; MADHURA S. BHOSALE (International Journal of Pharma and Bio Sciences, 2017)
Nishamalaki (NA), combination formulation of Curcuma longa and Emblica officinalis effective in diabetes as per Ayurvedic literature. We assessed the time required for development of diabetes and its complication with Streptozotocin (STZ) & High Fat High Fructose (HFHF) diabetic model. Objective was to evaluate NA for prophylactic, therapeutic efficacy and effectiveness in diabetic complication in rats. Diabetes induced in rats with STZ 35mg/kg i.p. + Followed by HFHF Diet till the development of Diabetes. Part I-Nishamalaki started with STZ, in (N= 25) of either sex compared with control rats. Part II- 30 Diabetic rats of either sex, randomly allocated to different groups (n=6), six rats allocated to control group with no diabetes and vehicle treatment. Groups I- vehicle, II- Diabetic Control, III-Nishamalaki (0.9 gm/kg), IV-Nishamalaki (1.8 gm/kg), V-Glibenclamide, VI- Pioglitazone and treated for 8 wks. Body weight, Blood sugar (BSL) & Lipid profile measured. Observed for complications for further 8 months. Statistical Analysis done with ANOVA. Persistent increased levels of BSL obtained in14 days. Nishamalaki achieved Significant (p<0.01) lowering of blood glucose and reduced serum cholesterol, triglycerides and LDL compared to diabetic control. Significant reduction in BSL observed in NA-LD (p<0.05) & Glibenclamide (p<0.01). Results of NA-HD were comparable to Pioglitazone. Serum Cholesterol levels significantly decreased in NA-LD (p< 0.001) & NA-HD (p< 0.01) than diabetic control. NA-LD, Glibenclamide & Pioglitazone were equal in reducing triglycerides (p< 0.01). HDL levels increased with NA-HD (p<0.001). Nishamalaki has major prophylactic value & Corrected lipid imbalance. Nishamalaki delayed development & progression of cataract, nephropathy & neuropathy.